2023
DOI: 10.1038/s41598-023-28872-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace amount of iron cations using electrochemical methods at N, S doped GQD modified electrode

Abstract: In this work, nitrogen and sulfur co-doped graphene quantum dot-modified glassy carbon electrodes (N, S-GQD/GCE) were used for the recognition of iron cations in aqueous solutions. The dissolved cations are detected based on the faradaic reduction or oxidation current of Fe(III) and Fe(II) obtained at the N, S-GQD/GCE surface. Cyclic voltammetry (CV), square wave voltammetry (SWV), and hydrodynamic amperometry are used as suitable electrochemical techniques for studying electrochemical behavior and determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…After synthesizing N, S:GQD as reported in previous work and in Supplementary Information (SI) 39 , 0.04 g of synthesized N, S:GQD in 20.0 mL of water was sonicated for 30 min to form a clear solution. Then slowly and under mechanical stirring, nickel ferrite (0.04 g) was added to the mixture, and the mixture was heated to 100 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After synthesizing N, S:GQD as reported in previous work and in Supplementary Information (SI) 39 , 0.04 g of synthesized N, S:GQD in 20.0 mL of water was sonicated for 30 min to form a clear solution. Then slowly and under mechanical stirring, nickel ferrite (0.04 g) was added to the mixture, and the mixture was heated to 100 °C.…”
Section: Methodsmentioning
confidence: 99%
“…GQDs are usually functionalized or doped with different heteroatoms to enhance intrinsic properties and change electronic structures 26 31 . Doping multiple heteroatoms attracted a lot of attention because it increases the holes on the surface of quantum dots increasing their conductivity and electrochemical activity 32 39 . It is concluded that the problem of low electrical conductivity of ferrites can be solved by composing them with heteroatom-doped GQDs, which makes it possible to use them as electrode modifiers with improved performance and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers represent a novel class of photoprotective materials with high activity against both UV and visible light. Key members of this class include polypyrrole, polyaniline and polythiophene and their derivatives [14,15]. Extensively explored and applied, these conjugated polymers have found utility as supercapacitor electrodes and in cancer cell ablation.…”
Section: Introductionmentioning
confidence: 99%